Conversation with Meir Sternberg (ENTHYMEMA, 2011)
Below are the videos of the interview recorded the 21st May 2011 in Fribourg (CH), in occasion of the first RRN conference.Conversation with Meir Sternberg.Part 1 of 8 - Narratology: classical and postclassical studies. Part 2 of 8 - The development of an original theoretical framework. Part 3 of 8 - Sternberg and Genette: different ways for the same problems. Part 4 of 8 - «There are no forms except in terms of functions». Part 5 of 8 - A life writing articles: so many papers and just four books. Part 6 of 8 - Two arguments against mimetical approaches to narrative. Part 7 of 8 - «Narrative is not given, it is a construct». Part 8 of 8 - The proteus principle. the many-to-many correspondence between forms and functions.
Keywords: Meir Sternberg; Tel Aviv school; functionalism; rhetoric; narrative